KINERJA PUTARAN ROTOR TURBIN AIR SCREW ARCHIMEDES DENGAN VARIASI KEMIRINGAN SUDUT TURBIN - Wijianti, Eka Sari (Jurusan Teknik Mesin Fakultas Teknik Universitas Bangka Belitung, 2021)
The Archimedes Screw Turbine is a micro hydropower plant that works to generate electrical energy. The source of water flow from this power plant has a low head so it is suitable for use in small flows such as irrigation and small rivers. The turbine is designed and then built to form a prototype with a screw length of 1 m, an outer diameter of 0.3 m, a number of blades 15, and a pitch distance of 13 cm each. The research was conducted with variations of the turbine inclination angle of 30o, 35o, and 40o. The results showed that the best rotor rotation was produced by an angle of 40o. The rotation that can be generated with a head of 0.67 m, the flow rate of 7 liters/second is 930 Rpm with an electric power potential of 43.95 watts.